Characteristics and composition of fractional products from pumpkin seeds - Kalyna, Viktoriia; Калина, Вікторія Сергіївна; Kondratiuk, Nataliia; Кондратюк, Наталія; Uvarova, Nataliia; Уварова, Наталія; Rozghon, Oleksandr; Розгон, Олександр; Bohuslavskyi, Viktor; Богуславський, Віктор; Lytsenko, Maryna; Луценко, Марина (Oles Honchar Dnipro National University, 2021)
The analysis of scientific and technical information on the determination of the chemical composition of pumpkin seeds fractional products is carried out. Recommendations on the use of pumpkin seeds fractional products in food products are given. A set of methods for determining the quality of pumpkin seeds and its fractional products is substantiated. The technological scheme of complex processing of pumpkin seeds is developed, the main elements of which are pressing of seeds and fractionation of crushed cake. Target products were obtained in the amount of: oil – 34 %, flour – 5 %, protein powder – 15 %, fiber – 46 %. The energy and biological value of the obtained fractions is calculated. The fatty acid composition of pumpkin oil and its ratio of fatty acids SFA : PUFA : MUFA = 10:38:42, indicating the feasibility of recommending pumpkin oil as a source of mono- and polyunsaturated fatty acids, are determined. The amino acid composition of protein powder is established, the content of all essential amino acids is proved, which characterizes its high biological value. According to the results of toxicological and microbiological tests of laboratory samples of pumpkin seeds fractional products, a high level of safety of these products has been established. Organoleptic and physico-chemical quality parameters of the obtained samples are determined, which meet the established norms for the analogous products and also testify to the high quality of the food products made by the suggested method. It is recommended to use the obtained products as independent in the diet of people and farm livestock or as supplements of traditional dishes or foodstuffs to enrich the nutrients and essential substances of human diets and foodstuffs for poultry, fish and domestic animals. За результатами досліджень розроблено технологічну схему комплексної переробки насіння гарбуза, основними елементами якої є пресування насіння та фракціонування подрібненої макухи. Одержано цільові продукти у кількості: олія – 34%, борошно – 5%, протеїновий порошок – 15%, клітковина – 46%. Розраховано енергетичну та біологічну цінність одержаних продуктів з насіння гарбуза. Визначено: жирнокислотний склад гарбузової олії, співвідношення жирних кислот складає НЖК:ПНЖК:МНЖК=10:38:42; вміст вітамінів Е та А у гарбузовій олії, кількість яких прирівнюється до рекомендованої добової норми; амінокислотний склад у протеїновому порошку, який містить увесь комплекс незамінних амінокислот, що характеризує його високу біологічну цінність; вміст мікотоксинів у протеїновому порошку, який відповідає вимогам нормативних документів. Досліджено та встановлено органолептичні і фізико-хімічні показники якості одержаних зразків продуктів переробки насіння гарбуза. Розроблено технічні умови на нові харчові продукти (Олія з насіння гарбуза. Технічні умови ТУ У 10.4-39224310-004:2019. Борошно з насіння гарбуза, клітковина з насіння гарбуза, протеїновий порошок з насіння гарбуза. Технічні умови. ТУ У 10.41-39224310-004:2021).
Характеристика і склад фракційних продуктів з насіння гарбуза
Keywords: pumpkin seed fractions; продукти переробки насіння гарбуза; pumpkin oil; олія; pumpkin seed flour; борошно; pumpkin seed protein powder; протеїновий порошок; cellulose; клітковина; functional products; показники якості